Untouchable Bodies, Resistance, and Liberation: A Comparative Theology of Divine Possessions: oleh Joshua Samuel - Adrianus Yosia (Asosiasi Teolog Indonesia, 2022)
This is a book review of Untouchable Bodies, Resistance, and Liberation: A Comparative Theology of Divine Possessions.